Hepatitis B Virus Infection among Health Care Workers in Indonesia - H Muljono, David (Euroasian J Hepatogastroenterol, 2018)
Hepatitis B virus (HBV) infection is a global health problem with an estimated 257 million chronically infected people. Indonesia is a moderately hepatitis B-endemic country with 7.1% prevalence of hepatitis surface antigen (HBsAg). This infection is considered as an important occupational hazard among health care workers (HCWs), who may become further transmitters of this infection. The extent of hepatitis B among HCWs and specific control strategy are not available in Indonesia. A study was done on 644 HCWs, who were categorized into administration, nonintervention, and intervention groups. The prevalence of HBsAg, antibody to HBV core antigen (anti-HBc), and antibody to HBsAg (anti-HBs) was 4.7, 18.5, and 36.7% respectively, while 57.3% were negative for all seromarkers, indicating susceptibility to this infection. Increasing trend with age was observed in the exposure to infection (anti-HBc) (p <0.001) and the marker of resolved infection (HBsAg-, anti-HBc+, anti-HBs+) (p = 0.004), suggesting accumulated exposure to HBV infection by increasing age. Rising trend of exposure rate was also observed across the administration, nonintervention, and intervention groups (p < 0.001). By length of service period, significant escalation of exposure (p = 0.010) and resolved infection (p < 0.001) were also observed, suggesting increasing occupational risk to HBV infection. There is an urgent need to safeguard the HCWs with hepatitis B vaccination and provide continuing education at various health care setups. The establishment of a national policy and a roadmap for effective and efficient intervention is required for the prevention, diagnosis, postexposure management, and treatment of HBV infection in this special population. How to cite this article: Muljono DH, Wijayadi T, Sjahril R. Hepatitis B Virus Infection among Health Care Workers in Indonesia. Euroasian J Hepato-Gastroenterol 2018;8(1):88-92.